East African mid-Holocene wet-dry transition recorded in palaeo-shorelines of Lake Turkana, northern Kenya Rift - (:unkn) unknown (My University, 2012)
The 'wet' early to mid-Holocene of tropical Africa, with its enhanced monsoon, ended with an abrupt shift toward drier conditions and was ultimately replaced by a drier climate that has persisted until the present day. The forcing mechanisms, the timing, and the spatial extent of this major climatic transition are not well understood and remain the subject of ongoing research. We have used a detailed palaeo-shoreline record from Lake Turkana (Kenya) to decipher and characterise this marked climatic transition in East Africa. We present a high-precision survey of well-preserved palaeo-shorelines, new radiocarbon ages from shoreline deposits, and oxygen-isotope measurements on freshwater mollusk shells to elucidate the Holocene moisture history from former lake water-levels in this climatically sensitive region. In combination with previously published data our study shows that during the early Holocene the water-level in Lake Turkana was high and the lake overflowed temporarily into the White Nile drainage system. During the mid-Holocene (~ 5270 ± 300 cal. yr BP), however, the lake water-level fell by ~ 50 m, coeval with major episodes of aridity on the African continent. A comparison between palaeo-hydrological and archaeological data from the Turkana Basin suggests that the mid-Holocene climatic transition was associated with fundamental changes in prehistoric cultures, highlighting the significance of natural climate variability and associated periods of protracted drought as major environmental stress factors affecting human occupation in the East African Rift System.
Keywords: African Research